Respuesta :
Answer:
c = -5
Step-by-step explanation:
Plug in -5 to c in the equation:
c² - 25 = 0
(-5)² - 25 = 0
Simplify. First, solve the power, then solve the subtraction:
(-5)² - 25 = 0
(-5 * -5) - 25 = 0
(25) - 25 = 0
0 = 0 (True)
~
Answer:
c=-5
Step-by-step explanation:
c^2-25=0
I'm going to solve this by using square root after I get the square termed by itself.
[tex]c^2-25=0[/tex]
Add 25 on both sides:
[tex]c^2=25[/tex]
Square root both sides:
[tex]c=\pm \sqrt{25}[/tex]
[tex]c=\pm 5[/tex]
Check!
[tex](5)^2-25=0 \text{ and } (-5)^2-25=0[/tex]